ESTABLISHMENT OF PROCESS OF APPLYING ENZYME AND COMBINATION TECHNICS TO OBTAIN FISH OIL RICH IN POLYUNSATURATED FATTY ACIDS CONTAINING EPA, DPA, DHA FROM RENDERED PRODUCTS OF TUNA THUNNUS ALBACARES - Bich, Hoang Thi; Anh, Nguyen Van Tuyet; Quan, Pham Minh; Hue, Pham Thu; Tung, Nguyen Quang; Toan, Tran Quoc; Thuy, Nguyen Thi; Toan, Hua Thi; Thanh, Le Tat (Vietnam Journal of Marine Science and Technology, 2017)
Products containing super long-chain polyunsaturated fatty acids of omega-3 group play an important role in the fields of medical, pharmaceutical and food industries. In nature, omega-3 fatty acids (n-3) are mainly present in marine organisms such as seaweed, corals, sea fish,... In this publication, we refer to the process of manufacturing the product with high levels of the super long-chain polyunsaturated fatty acids (Highly unsaturated fatty acids - HUFA) such as EPA, DHA and DPA (n-3) which includes steps such as raw materials treatment, segregation, cleansing, enrichment, refining to collect the product, from the rendered products (head and internal organs) of the types of tuna. In addition, the process also obtains by-products which are fish powder and soluble oligopeptides.